2012
DOI: 10.1177/0734282912436411
|View full text |Cite
|
Sign up to set email alerts
|

The Wechsler ACS Social Perception Subtest

Abstract: Relative to other cognitive areas, there are few clinical measures currently available to assess social perception. A new standardized measure, the Wechsler Advanced Clinical Solutions (ACS) Social Perception subtest, addresses some limitations of existing measures; however, little is known about this new test. The first goal of this investigation was to preliminarily explore the relationship of the ACS Social Perception subtest to five other measures of social perception and cognition in a sample of control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Social cognition was evaluated with the Wechsler Adult Intelligence Scale Advanced Clinical Solutions (ACS) Social Perception Subtest (WAIS-ACS). The assessment involves the detection of emotional states and meaning interpretation by appraisal of facial affect, prosody, and body language (32, 33). A previous study by Air et al (5) indicated that social cognitive abilities measured by the ACS were associated with mood and anxiety symptoms in currently depressed, but not remitted, individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Social cognition was evaluated with the Wechsler Adult Intelligence Scale Advanced Clinical Solutions (ACS) Social Perception Subtest (WAIS-ACS). The assessment involves the detection of emotional states and meaning interpretation by appraisal of facial affect, prosody, and body language (32, 33). A previous study by Air et al (5) indicated that social cognitive abilities measured by the ACS were associated with mood and anxiety symptoms in currently depressed, but not remitted, individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The RMET meta-analysis revealed no statistically significant difference in performance between groups, although SSDs groups performed slightly better than ASD groups (k = 13; g = 0.25 [95% CI, −0.04 to 0.53]; P = .10) (Figure 3C). 32,48,49,51,55,56,59,62,65,66,69,70,72 Effect sizes were statistically significantly and highly heterogeneous (I 2 = 75.3%), although no outliers were identified (Figure 2C and eTable 5 in the Supplement). Funnel plot visualization (eFigure 2C in the Supplement) and Egger regression test revealed no evidence of publication bias (Table 2).…”
Section: Reading the Mind In The Eyes Testmentioning
confidence: 97%
“…Greater I 2 statistics represent higher between-study heterogeneity. After outlier removal (where detected), forest plots for meta-analyses show standardized mean difference (Hedges g) and 95% CIs for emotion processing (A), 28,34,46,48,51,52,54,57,60,63,67-69,72,73 theory of mind (B), 28,34,46,48,51,52,54,57,60,63,[67][68][69]72,73 and the Reading the Mind in the Eyes Test (C). 32,48,49,51,55,56,59,62,65,66,69,70,72 Hedges g values exceeding 0 indicate that SSDs groups outperformed ASD groups.…”
Section: Emotion Processingmentioning
confidence: 99%
“…Among validated batteries allowing the assessment of both functions (emotion recognition and theory of mind), the TASIT and the mini Social cognition and Emotional Assessment [mini-SEA; (212)] offer good clinical sensitivity and specificity. Beyond these tools mostly developed for or with patients in neurodegenerative diseases, the Wechsler Advanced Clinical Solutions Social Perception subtest (282), the Edinburgh Social Cognition Test (283) and the EMOTICOM [for Emotion, Motivation, Impulsivity, and Social Cognition (284)] could offer alternative multi-dimensional assessments of social cognitive functions with less language load, but their applicability in neurodegenerative syndromes has not yet been assessed.…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 99%